Biallelic POC1A variants cause syndromic severe insulin resistance with muscle cramps. Issue 5 (23rd March 2022) - Mericq, Veronica; Huang-Doran, Isabel; Al-Naqeb, Dhekra; Basaure, Javiera; Castiglioni, Claudia; de Bruin, Christiaan; Hendriks, Yvonne; Bertini, Enrico; Alkuraya, Fowzan S; Losekoot, Monique; Al-Rubeaan, Khalid; Semple, Robert K; et al.
Abstract: Objective: To describe clinical, laboratory, and genetic characteristics of three unrelated cases from Chile, Portugal, and Saudi Arabia with severe insulin resistance, SOFT syndrome, and biallelic pathogenic POC1A variants. Design: Observational study. Methods: Probands' phenotypes, including short stature, dysmorphism, and insulin resistance, were compared with previous reports. Results: Cases 1 (female) and 3 (male) were homozygous for known pathogenic POC1A variants: c.649C>T, p.(Arg217Trp) and c.241C>T, p.(Arg81*), respectively. Case 2 (male) was compound heterozygous for p.(Arg217Trp) variant and the rare missense variant c.370G>A, p.(Asp124Asn). All three cases exhibited severe insulin resistance, acanthosis nigricans, elevated serum triglycerides and decreased HDL, and fatty liver, resembling three previously reported cases. All three also reported severe muscle cramps. Aggregate analysis of the six known cases with biallelic POC1A variants and insulin resistance showed decreased birth weight and length mean (s.d. ): −2.8 (0.9) and −3.7 (0.9) SDS, respectively), severe short stature mean (s.d. ) height: −4.9 (1.7) SDS) and moderate microcephaly (mean occipitofrontal circumference −3.0 (range: −4.7 to −1.2)). These findings were similar to those reported for patients with SOFT syndrome without insulin resistance. Muscle biopsy in Case 3 showed features of muscle involvement secondary to a neuropathic process. Conclusions: Patients with SOFT syndrome can develop severe dyslipidaemic insulin resistance, independent of the exonic position of the POC1A variant. They also can develop severe muscle cramps. After diagnosis, patients should be regularly screened for insulin resistance and muscle complaints.